A Comparative Assessment of Australian Student Visa Policy - Phillimore, John; Koshy, Paul (John Curtin Institute of Public Policy, Curtin University of Technology, 2010)
Following recent falls in international student commencements in Australia, there has been a renewed call for a revision to student visa policy. In response to this discussion the Commonwealth Government established the Knight Review of the Student Visa Program in December 2010. This paper discusses several policy options following acomparative analysis of student visa systems in Australia, the United States, the United Kingdom, Canada and New Zealand. The underlying fi nding is that Australia’s student visa system is more complex, more costly and imposes greater fi nancial obligations on international students and their families than comparable countries. Australia could benefi t from an overall simplifi cation of its student visa system, including a streamlining of the number of visas available to students and a reduction in the stringency of the tests applied in regard to financial capacity and proof of funding. In addition, attention should be paid to post-study employment options under the student visa system and the nexus between higher education attainment and immediate work options.